Simulation training program for midwives to manage postpartum hemorrhage: A randomized controlled trial. (April 2017) - Kato, Chiho; Kataoka, Yaeko
Abstract: Purpose: To explore the effectiveness of a simulation training program for midwives in performance and knowledge for the management of postpartum hemorrhage (PPH). Methods: The study design was a randomized controlled trial. Midwives working at one obstetrics ward in an urban area were randomly assigned to simulation training program or no training. This "simulation program" included pre study e-learning and simulation. Inclusion criteria were midwives who: 1) had two or three years of clinical experience, 2) worked in an obstetrics ward, and 3) had experience with birth assistance. There was one exclusion criterion namely prior experience of simulation training for PPH. Change in performance was evaluated using a PPH scenario performance test at one month after the simulation training. Change in knowledge was evaluated by a 25-item multiple-choice questionnaire completed shortly before the training and one month after the training. The ethical review committee of St Luke's International University granted approval (No. 14-096). Results: Eighty-one midwives were randomly assigned to either the intervention group ( n  = 40) or the control group ( n  = 41). Performance in the simulation training group was significantly better in comparison to the no training group; mean performance score was 23.85(SD 2.71) in the training group versus 18.00(SD 3.01) in the no training group (MD 5.85 95% CI 4.85–7.12, t  = 9.17, p  < 0.001). Knowledge was significantly increased in the simulation training group; amount of knowledge score was 3.65(SD 3.40) in the training group versus − 0.02(SD 3.02) in the no training group (MD 3.67 95% CI 2.25–5.10, t  = 5.14, p  < 0.001). Conclusion: Both performance and knowledge about the management of PPH were significantly improved after simulation training. However, assessments of long-term effects on performance, and knowledge and the clinical outcomes in managing of obstetric complications are necessary to adequately evaluate the effectiveness of simulation training. Highlights: Simulation-training group had a significantly higher performance scores than no training. Simulation training group had a significantly large variation in knowledge scores in prior and 1 month after training. Simulation-training group displayed more confidence in their ability to appropriately management of PPH.